Methods of constructing hyperfields - Ch. G. Massouros (International Journal of Mathematics and Mathematical Sciences)
In this paper we introduce a class of hyperfields which contains non quotient hyperfields. Thus we give a negative answer to the question of whether every hyperfield is isomorphic to a quotient KG of a field K by some subgroup G of its multiplicative group.